The Continuity of Marriage Ceremony of Bharsele Magar: A Study of Kathmandu Valley - Budhathoki , Hemanta (Patan Pragya, 2025)
This study related to marriage rituals of the Bharseli Magar of Kathmandu Valley consists of 92 households of Bharseli Magar of Kathmandu Valley, informant interview (KII) with 6 persons, and secondary data. The main aim of this article is to explain the socio-economic aspects and traditional marriage rituals of Bharseli Magars of Kathmandu Valley. There are 16 clans and 29 sub-clans of Magars included in the Bharseli Magars of Kathmandu Valley. Traditionally, the cross cousin /Tin Ghare/ Odane marriage system has been practiced. The traditional marriage consists of Magani, Sodhani, Dulahi Bhitryaune, Theki khane, Dhogbhet, Janti Jane, Dulhan Farkaune, Saipata Tirne etc. Additionally, in traditional marriage rituals of the Bharseli Magars, the bread, pickle, wine, curd, meat of chicken, and goat are used as the food items. In traditional marriage rituals the Dhiungri, Madauri, Kantha, Dhungri, Hammel, Bulanki, Har, Chura, Pote, etc. ornaments have been used in Marriage rituals of Bharseli Magars of Kathmandu Valley. There is a practice of wearing, Kachhad, Daura, Bhangra (Gada), and cap of thread by Magar men and Blauj, Lungi, Ghalek, Saul, etc. by the Magar women during the marriage ceremony. The arrange marriage, love marriage, forced marriage, and theft marriage are traditionally practiced by the Bharseli Magars of Kathmandu Valley. The objective of this article is to explore the socio-cultural status and traditional marriage rituals of Bharseli Magars of Kathmandu Valley.